1998
DOI: 10.13031/2013.17250
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Storage Study With Methyl and Ethyl Esters of Rapeseed

Abstract: B iodiesel is gaining recognition as a renewable alternative to diesel fuel. One step toward commercialization of biodiesel is establishing how well it stores and what affect storing for long periods has on the performance of the fuel. The problems of fuel deterioration with biodiesel during storage are expected to be more severe than for commercial diesel fuel. Although vegetable oils contain natural antioxidants, their high degree of unsaturation makes them susceptible to gum formation. Since fuel deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 5 publications
2
37
0
5
Order By: Relevance
“…Thus the chain breaking antioxidants help to interrupt the oxidation chain reaction in order to enhance . The results were in agreement with the literature findings [16][17][18][19][20][21]. When antioxidants are mixed with JCB, the oxidation process is retarded resulting in the decrease in relative percentage of oleic acid as shown in Figure 6(a) and increase in relative percentage of linoleic and linolenic acid indicating the retardation of oxidation process after the addition of PY (Figures 6(a), 6(b), and 6(c)).…”
Section: Design Of Experiments Using Rsmsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus the chain breaking antioxidants help to interrupt the oxidation chain reaction in order to enhance . The results were in agreement with the literature findings [16][17][18][19][20][21]. When antioxidants are mixed with JCB, the oxidation process is retarded resulting in the decrease in relative percentage of oleic acid as shown in Figure 6(a) and increase in relative percentage of linoleic and linolenic acid indicating the retardation of oxidation process after the addition of PY (Figures 6(a), 6(b), and 6(c)).…”
Section: Design Of Experiments Using Rsmsupporting
confidence: 91%
“…This is in agreement with the Das et al [16] who found that peroxide formation decreases with increase in antioxidant concentration, thereby leading to the lower rate of increase of viscosity that became lower. A number of reports confirm that the retardation of oxidation process became higher as the antioxidant concentration is increased [7,[16][17][18][19][20][21]. The reduced rate of peroxide formation led to the increase in long-term storage stability in terms of IP which indicates that it is possible to store biodiesel for longer period of time by adding the antioxidant.…”
Section: Design Of Experiments Using Rsmmentioning
confidence: 95%
“…In contact with oxygen, peroxides are formed that promote the formation of organic acids, and then of polymers (gums) that plug fuel lines and filters. Oxidative degradation during storage can also compromise fuel quality with respect to effects on kinematic viscosity, acid value, cetane number, total ester content, and formation of hydroperoxides, soluble polymers, and other secondary products (Du Plessis et al, 1985;Bondioli et al, 2002;Thompson et al, 1998). The increased acidity and peroxide values as a result of oxidation reactions can also cause the corrosion of fuel system components, the hardening of rubber components and the erosion of moving parts (Tang et al, 2008).…”
Section: The Needs For Refining Of Petrodiesel and Biodiesel Fuelsmentioning
confidence: 99%
“…Studies have shown that the development of ROOH over time exhibits one of two behaviors. First, ROOH levels can increase, achieve a plateau, and then hold that level in a steady state 4,50,87,95,100,101,106 . Alternatively, ROOH levels can increase, achieve a peak level, and then decrease 4,50,70,96,106,117 .…”
Section: Figure 3 Reaction Schemementioning
confidence: 99%
“…Aliphatic alcohols, formic acid, and formate esters have also been detected 32,55 . Increased acidity is always a result of oxidation of fatty oils and biodiesel 50,87,100,101,106 , due to the formation of shorter chain fatty acids 32,101 . As hydroperoxides decompose, oxidative linking of fatty acid chains can occur so as to form species with higher molecular weights, i.e.…”
Section: Secondary Products Of Oxidationmentioning
confidence: 99%